Halide‐Ion Diadducts of Perhalogenated Cyclopenta‐ and Cyclohexasilanes. Issue 17 (8th June 2018) - Teichmann, Julian; Köstler, Benedikt; Tillmann, Jan; Moxter, Maximilian; Kupec, Robin; Bolte, Michael; Lerner, Hans‐Wolfram; Wagner, Matthias
Abstract : The halosilicates(II) [ n Bu4 N]2 [Si6 Br12 · 2Br] and [ n Bu4 P]2 [Si6 I12 · 2I] were prepared by mere addition of the appropriate halide salt to the corresponding disilane Si2 X 6 ( X = Br, I). In the first case, the Br3 Si‐substituted derivative [ n Bu4 N]2 [Si7 Br14 · 2Br] formed as a second product. We have been able to obtain single crystals of [Ph4 P]2 [Si7 Br14 · 2Br] by switching the Br – salt from [ n Bu4 N]Br to [Ph4 P]Br. All three compounds, [ n Bu4 N]2 [Si6 Br12 · 2Br] (monoclinic, P 21 / c ), [ n Bu4 P]2 [Si6 I12 · 2I] (triclinic, P 1 ), and [Ph4 P]2 [Si7 Br14 · 2Br] (triclinic, P 1 ) were structurally characterized by X‐ray crystallography and found to form "inverse sandwich complexes", in which two X – ions are located above and below a planarized Si6 ring. The free periodated cyclohexasilane Si6 I12 is accessible from [ n Bu4 N]2 [Si6 Cl12 · 2Cl] and BI3 (1:5 molar ratio; CH2 Cl2 ) via a decomplexation/halide‐exchange cascade. Si6 I12 (monoclinic, C 2/ c ) adopts a puckered chair conformation in the solid state. The cyclopentasilane diadduct [ n Bu4 P]2 [Si5 Cl10 · 2Cl] forms at –78 °C from Si5 Cl10 and 2 equiv. of [ n Bu4 P]Cl in CH2 Cl2 . An X‐ray analysis of [ n Bu4 P]2 [Si5 Cl10 · 2Cl]· 2CH2 Cl2 (monoclinic, C 2/ c ) again revealed the structure of an "inverse sandwich complex". Crystalline [ n Bu4 P]2 [Si5 Cl10 · 2Cl]· 2CH2 Cl2 is stable at room temperature. However, in CH2 Cl2 solution the compound quantitatively undergoes ring‐expansion reactions to furnish cyclohexasilane derivatives. This behavior is in striking contrast to that of [ n Bu4 N]2 [Si6 Cl12 · 2Cl], which persists at room temperature both in solution and the solid state. Competition experiments revealed free Si5 Cl10 and Si6 Cl12 to have comparable Cl – affinities, even though the distance between the two apical Cl – ions in [Si5 Cl10 · 2Cl] 2– (4.292 Å) is larger by 0.456 Å than that in [Si6 Cl12 · 2Cl] 2– (3.836 Å). Abstract :